A new species of the genus Macronychus Müller, 1806 from China (Coleoptera, Elmidae) - Jiang, Ri-Xin; Chen, Xiang-Sheng (Zootaxa, 2024)
Macronychus xuhaoi sp. nov., a new species of the genus Macronychus Müller, 1806 is described from Xizang, Southwest China. The new species belongs to Macrynychus quadriluberculatus species group. Habitus and other diagnostic features of the new species are described and illustrated.